“We Are Changed by What We Change”: W. H. Auden’s New Year Letter - Rowland Cotterill (Acta Universitatis Wratislaviensis. Anglica Wratislaviensia)
This paper considers representations of change, internal and external to a changeable and changing subject, in W. H. Auden’s New Year Letter. This long poem focuses on three aspects of change: personal responses to a sense of accountability, as experienced especially by poetic artists; diagnoses of change, across three historical epochs, within a world exposed at once to individual and public pressures, most recently those of crowd-consciousness and Fascist dictatorship; and a possible embrace of performative genres and modes, including dramatic conversation and Horatian epistolography, through which these lines of personal and conceptual discourse may tend towards convergence.